Quantitative dynamics of telomere bouquet formation. - David M Richards; Emma Greer; Azahara C Martin; Graham Moore; Peter J Shaw; Martin Howard (PLoS Computational Biology)
The mechanism by which homologous chromosomes pair during meiosis, as a prelude to recombination, has long been mysterious. At meiosis, the telomeres in many organisms attach to the nuclear envelope and move together to form the telomere bouquet, perhaps to facilitate the homologous search. It is believed that diffusion alone is not sufficient to account for the formation of the bouquet, and that some directed movement is also required. Here we consider the formation of the telomere bouquet in a wheat-rye hybrid both experimentally and using mathematical modelling. The large size of the wheat nucleus and wheat's commercial importance make chromosomal pairing in wheat a particularly interesting and important process, which may well shed light on pairing in other organisms. We show that, prior to bouquet formation, sister chromatid telomeres are always attached to a hemisphere of the nuclear membrane and tend to associate in pairs. We study a mutant lacking the Ph1 locus, a locus ensuring correct homologous chromosome pairing, and discover that bouquet formation is delayed in the wild type compared to the mutant. Further, we develop a mathematical model of bouquet formation involving diffusion and directed movement, where we show that directed movement alone is sufficient to explain bouquet formation dynamics.